Roles beyond Instruction: Facilitating the Development of Preservice Teachers - Yvonne Franco (Networks: An Online Journal for Teacher Research, 2014)
Identifying a Signature Pedagogy that ensures high-quality teacher preparation is essential to the field of teacher education, as inconsistencies across programs throughout our country threaten our profession. Drawing on a comprehensive study of the professions, Lee Shulman (2005) provides a lens from which to identify Signature Pedagogy and the underlying experiences that support it, as pedagogies of uncertainty, engagement, and formation. As a teacher-educator, this action research study examines my efforts in understanding how I can use my knowledge of Signature Pedagogy to design, implement and study practices that facilitate pre-service teachers’ conceptualization of the teacher’s role beyond instruction. Using Shulman’s lens, I identify specific pedagogical experiences that lead to developing this conceptualization, and explore the critical role of the teacher educator in ensuring the effectiveness of these experiences.